STRATEGY OF LIBRARY DEVELOPMENT TOWARDS DIGITAL LIBRARY - Muhammad Ainul Yaqin (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2022)
This study intends to analyze the strategy for developing the library of the University of Nurul Jadid Paiton Probolinggo towards a digital library in increasing competitiveness in the current era of globalization. This study uses a qualitative approach analysis. This research has implications for library development in order to meet and match community competition in improving the quality of the library. The efforts made in developing libraries towards digital libraries by building information accessibility, digital library development strategies in building information accessibility through an organizational approach to digital library management funds, digital library technology implementation approaches, access policy approaches and information legality, and values ​​transformation approaches. cultural diversity value. So this is expected to be able to develop the library towards a quality digital library